2010
DOI: 10.1080/10888700903369248
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Substrate Access Did Not Affect Early Feather-Pecking Behavior in Two Strains of Laying Hen Chicks

Abstract: Feather pecking, commonly found in flocks of laying hens (Gallus gallus), is detrimental to bird welfare. Thought to cause this problem is the normal housing of layers without a floor substrate. Some evidence suggests that early substrate access decreases later feather pecking. However, there has been little research on the immediate effects of a change in substrate availability on bird welfare, although environmental modifications like this are often done when brooding and rearing laying hen chicks. To invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
2
5
0
3
Order By: Relevance
“…Therefore, the authors concluded that a suitable feed substrate promotes foraging behaviour and SFP reduction or even delay. Similar results were obtained by Dixon & Duncan, , who also observed that sand‐bath substrates, when provided as the only manipulable material in the husbandry environment, are not able to reduce SFP. In this comparison, chicks were kept on wired floors or on solid floors covered with peat moss.…”
Section: Effects Of Littersupporting
confidence: 87%
“…Therefore, the authors concluded that a suitable feed substrate promotes foraging behaviour and SFP reduction or even delay. Similar results were obtained by Dixon & Duncan, , who also observed that sand‐bath substrates, when provided as the only manipulable material in the husbandry environment, are not able to reduce SFP. In this comparison, chicks were kept on wired floors or on solid floors covered with peat moss.…”
Section: Effects Of Littersupporting
confidence: 87%
“…In line with his observations, Huber-Eicher and Wechsler (1997) found that access to straw, a foraging substrate, did decrease FP, but access to sand, a dustbathing substrate, did not or only to a limited extent. This is supported by a study showing that peat in early rearing (that is preferred for dustbathing but not for foraging) did not reduce early FP behaviour (Dixon and Duncan, 2010). In a study by Johnsen et al(1998), pullets were raised on sand, straw, or wire between 0-4 weeks of age.…”
Section: Causes Of Feather Pecking and The Importance Of Littermentioning
confidence: 86%
“…현재 피트모스에 대한 국내 연구로는 농업과 원예분야에 서 토양의 활용방안에 대한 연구가 대부분이고 (Park et al, 2013;Kim et al, 2011;Na et al, 2013), 국외에서는 축산업에 관련된 연구는 아주 제한적이다 (Dixon and Duncan, 2010;Meng et al, 2015). 최근에는 항염증제로서 피트모스 추출물 의 효과에 대한 연구 결과가 발표되었다 (Choi et al, 2014 (Feddes et al, 2002;Ghazi et al, 2014 본 연구에서는 사료첨가제로서 피트모스 추출물이 육계 의 생산성에 미치는 영향을 조사하였다.…”
unclassified
“…지금까지 피트모스 는 식물의 성장촉진제 또는 비료 대체제로 많이 이용되고 있 고 (Hu et al, 2009;MacCarthy, 1976), 국내에서는 농업과 원 예분야에서 토양의 활용방안에 대한 연구가 대부분일 뿐 (Park et al, 2013;Mihyang et al, 2011;Na et al, 2013), 축산분야 에서 이용된 적은 없었다. 국외 축산 연구에서는 소수의 연 구자들이 바닥재로서 피트모스의 가능성에 대하여 연구하였 을 뿐이다 (Dixon and Duncan, 2010;Meng et al, 2015). 여 러 가지 바닥재의 재료들 중 피트모스의 비율을 적절히 조 정한다면, 사육환경의 질을 높이는 효과를 볼 수 있다.…”
unclassified
See 1 more Smart Citation